Lolium multiflorum germination and growth affected by virgin, naturally, and artificially aged high-density polyethylene microplastic and leachates - Esterhuizen, Maranda; Vikfors, Sofia; Penttinen, Olli-Pekka; Kim, Young Jun; Pflugmacher, Stephan (Frontiers in Environmental Science, 2022)
With the detection of microplastics in soil, coupled with the various sources continuously contributing to its delivery to and distribution in soils, understanding the effects of microplastics on plants are necessary. Plastics discarded in the environment continually degrade into micro- and nano-sizes, subsequently leaching hazardous chemicals with time. Not only time but also environmental factors related to the climate of the area where the plastic is degrading will contribute to the breakdown process. Thus, this study aimed to understand the phytotoxic effects of microplastic derived from a frequently discarded plastic item, i.e., high-density polyethylene soda bottle caps. The commonly occurring perennial Lolium multiflorum (Italian ryegrass) was exposed to microplastic derived from new and artificially aged bottle caps as well as bottle caps collected from the cities of Lahti, Finland and Gqeberha, South Africa. Additionally, leachates were prepared from these samples and used for exposure. Germination, root and shoot growth, and fresh weight were measured as indicators of adverse effects, and various growth parameters were calculated. Microplastic and leachates from new and Lahti collected bottle caps adversely affected the germination and growth of the plant, indicating that aging and environmental factors affect the phytotoxicity of plastics as environmental pollutants in soil.